Adherence Level Of Medical Personnel In Implementing 2019 Postoperative Pain Management Guidelines - Nasrulloh Nasrulloh; Hamzah Hamzah; Arie Utariani; Dedi Susila (Universitas Nahdlatul Ulama Surabaya, 2021)
Introduction: Inadequate pain management may increase the risk of complications and postoperative chronic pain. Postoperative Pain Management Guidelines of The Anesthesiology and Reanimation Department, Faculty of Medicine Universitas Airlangga/ Dr. Soetomo Hospital Surabaya were arranged in 2019. Purposes: This study aim is to analyze the medical personnel’s adherence in implementing postoperative pain management guidelines. Methods: This is descriptive observational study with retrospective design. Total sampling was carried out on the medical records of patients who underwent elective surgery and received postoperative acute pain management during March-May 2020. Results: A total of 349 patients, most of the pain intensity was moderate (62.8%). The medical personnel adherence with postoperative pain management guidelines was 88.0%. The overall use of multimodal analgesia was 61.0%. Adherence to guidelines on pain category was mostly good adherence: 99.1% in mild pain, 82.6% in moderate pain, and 81.2% in severe pain. The use of multimodal analgesia was found in 12.3% mild pain; 83.6% moderate pain, and 100% severe pain patients. Conclusion: Most of the medical personnel have adhered to the postoperative pain management guideline, and widely-used multimodal analgesia. Systematic evaluation of guidelines implementation, patient satisfaction, and outcomes are needed.